Pendekatan Connectivisme Theory dalam pembelajaranMaharah Kalam berbasis Digital Visual Literacy (DVL) - Hajar Nurma Wachidah (Institut Muslim Cendekia, 2024)
This research is intended to contribute to finding interesting and significant learning according to the digital era in developing students' Arabic literacy skills through the connectivism approach. By formulating and compiling visual literacy-based teaching materials to support the achievement of maharah kalam teaching objectives to be achieved can run systematically. Qualitative methods as well as Spradley's analysis model were used in this study with 78 correspondents in Islamic University. The results stated that the Connectivism Approach of online learning is seen as a connection between educators and students because it makes it easier to share knowledge with digital teaching materials that support teaching and learning activities so that there is a close relationship through the Internet of things (IoT). Diversity in the connectivism approach views that learning Arabic, especially maharah kalam, feels unique and useful for all groups, this is because the features displayed in the visual literacy digital teaching material media have been made by the lecturer in charge of the course very interesting and easy to access on the website.